Основные тенденции развития системы фондов СО РАН (Библиосфера, 2010)
The results of a system formation and corporate models of libraries co-operation for SB RAS libraries are considered, the main factors influencing the strategy of formation of academic libraries resource base are determined, highlighted are the problems of formation of new types of resources and the prospects for their inclusion in the information resource base of SB RAS are outlined.